Moderasi Beragama: Moderasi Beragama dalam Geguritan Dharma Sunyata - Ni Wayan Apriani; Ni Komang Aryani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This study aims to determine the moderating value contained in Geguritan Dharma Sunyata. The data in this study were collected using document study techniques. Furthermore, it is analyzed with the stages of data reduction, data presentation and drawing conclusions. From the results of data analysis, it was found that the value of religious moderation contained in Geguritan Dharma Sunyata was based on the teachings of Tat Twam Asi and Tri Kaya Parisudha. Tat Twam Asi's teachings are the basis of Hindu ethics in an effort to achieve moral improvement. Tat Twam Asi is a teaching that states the similarities between individuals so that it gives birth to the concept of compassion for all creatures in the world. Religious people should respect and appreciate each other even though they adhere to different religions.